Representation of President Valdas Adamkus in the US and UK press (1998–2012) - Grinevičiūtė, Agnė (Žurnalistikos tyrimai, 2011)
This article aims to review the representation of former Lithuanian president Valdas Adamkus in a number of US and UK online publications between 1998 and 2011. To achieve this, the following topics are discussed: political communication with the authorities and the press, writing tendencies in individual essays and main topics related to the president. Additionally, a list of all used publications is provided alongside the findings. This type of study has never been done before. It is significant as it portrays the representation of President Valdas Adamkus in the most important publications in the world during a crucial time, when Lithuania was seeking recognition in the international arena, i.e. aiming to join NATO and the EU. The practical part of this work evaluates the President’s position on various topics, and theoretical consequences that his views might have caused Lithuania. Additionally, it assesses how the aforementioned publications portrayed not just Valdas Adamkus, but also our country, since the image of the head of state is often identified with the image of his or her country. The research results have revealed that selected publications provided their audience with very limited information about the Lithuanian President. His portrayal appears fairly shallow and incomplete, focusing mainly on his personality. However, they highlight the President’s aspiration to join NATO and the EU. As expected, the portrayal of the Lithuanian leader differs in various publications. This article consists of the following: an introduction, subsections on political communication, the meaning and importance of political image and the media as a key participant in political communication. Since this article focuses on Valdas Adamkus, a brief summary of his biography, work and achievements will be provided. Systemised research results will be discussed in the practical part of this article. Research findings and bibliography will be presented in the end. Keywords: reflection, image, presentation, periodic literature, political communication, president, representation, foreign policy.